The impact of financial risk on stock returns in the Jordanian commercial banks during the period (2007-2016) - Alaa A Abu Aleem; Mohamed Zaoui; Jum’a M Abbad (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
This study aimed at measuring the impact of financial risks represented by (liquidity risk, credit risk and solvency risk) on the stocks return of Jordanian commercial banks. The study was conducted on the Jordanian banking sector consisting of thirteen Jordanian commercial banks during the period (2007-2016). In order to estimate the impact of financial risk on stocks returns, the study used  Panel data analysis method. In order to test hypotheses, based on the Hausman test the random effect model was used between independent variables (liquidity risk, solvency risk, and credit risk) and stocks returns.